2012
DOI: 10.1029/2012gl051148
|View full text |Cite
|
Sign up to set email alerts
|

Strong radiative heating due to wintertime black carbon aerosols in the Brahmaputra River Valley

Abstract: The Brahmaputra River Valley (BRV) of Southeast Asia recently has been experiencing extreme regional climate change. A week‐long study using a micro‐Aethalometer was conducted during January–February 2011 to measure black carbon (BC) aerosol mass concentrations in Guwahati (India), the largest city in the BRV region. Daily median values of BC mass concentration were 9–41μgm−3, with maxima over 50 μgm−3during evenings and early mornings. Median BC concentrations were higher than in mega cities of India and Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In India, several studies are reported over the IndoGangetic Plains (Tripathi et al, 2005;Nair et al, 2007;Dumka et al, 2010;Ramachandran and Kedia, 2010;Praveen et al, 2012;Srivastava et al, 2012;Tiwari et al 2013a;Srivastava and Ramchandran, 2013;Kanawade et al, 2014;etc. ) as well as the eastern part of India (Das, 2010;Pathak et al, 2010;Chatterjee et al, 2012;Chakrabarty et al, 2012;Sarkar et al, 2014;etc.). In the present study, continuous measurement of BC mass concentrations was made for the first time over the coal field area in Dhanbad, India.…”
Section: Introductionmentioning
confidence: 99%
“…In India, several studies are reported over the IndoGangetic Plains (Tripathi et al, 2005;Nair et al, 2007;Dumka et al, 2010;Ramachandran and Kedia, 2010;Praveen et al, 2012;Srivastava et al, 2012;Tiwari et al 2013a;Srivastava and Ramchandran, 2013;Kanawade et al, 2014;etc. ) as well as the eastern part of India (Das, 2010;Pathak et al, 2010;Chatterjee et al, 2012;Chakrabarty et al, 2012;Sarkar et al, 2014;etc.). In the present study, continuous measurement of BC mass concentrations was made for the first time over the coal field area in Dhanbad, India.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Zhang et al proved that haze pollutants comprise particles both from local emission sources and from long distance transport [23]. Owing to weather patterns, particles can be transferred on the continental scale, which greatly affects the air quality of locations in downwind directions [24,25]. Furthermore, Li et al and Duan et al studied the phase and mixture status of aerosols and discovered that hazes in the North China Plain (NCP) during June are caused primarily by particles generated from the combustion of agricultural biomass [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence it may be concluded that this enhanced BC absorption inside the cloud is giving way to a reduction of albedo at TOA and enhancing the atmospheric absorption. Chakrabarty et al () reported a direct forcing of −63.4 W m −2 by BC at the surface and +11.2 W m −2 at TOA over GHT for clear‐sky days (in the winter season for a similar BC mass concentration). Hence our study suggests that in cloudy conditions, the BCIF at the surface may contribute around half the magnitude of direct forcing; however, its contribution may be equal to or greater than BC direct forcing at TOA.…”
Section: Resultsmentioning
confidence: 99%